Strategies to preventing pressure injuries among intensive care unit patients mechanically ventilated in prone position: a systematic review and a Delphi study - Wang, Zonghua; Fan, Jiangshan; Chen, Ling; Xie, Langlang; Huang, Lingfang; Ruan, Yang; Xu, Xia; Liang, Zeping (Frontiers in Medicine, 2023)
Background Although the incidence of pressure injury in the prone position is high for the mechanically ventilated patients in the intensive care unit, evidence-based strategies are still lacking.Propose To conduct a systematic review of current evidence, and to propose a series of strategies to prevent pressure injuries among mechanically ventilated patients with prone position in the intensive care unit.The study was guided by the Medical Research Council framework. After a systematic review of current evidence of original articles, guidelines, expert